Matrix Remodeling-Associated Protein 5 in Urinary Exosomes as a Potential Novel Marker of Obstructive Nephropathy in Children With Ureteropelvic Junction Obstruction - Wang, Qi; Shi, Zhengzhou; Xing, Xiaoyu; Deng, Yiting; Li, Wenjie; Xie, Tianwei; Jiang, Dapeng (Frontiers in Pediatrics, 2020)
Recent investigations described the use of urinary matrix remodeling-associated protein 5 (MXRA5) as a novel biomarker for kidney impairment in the setting of chronic kidney disease. In this study, we aimed to evaluate the possible clinical application of urinary MXRA5 as a useful noninvasive marker in the urine from affected renal pelvis and bladder in children with ureteropelvic junction obstruction (UPJO). This prospective cohort study enrolled patients aged <12 months with prenatally diagnosed unilateral UPJO who received dismembered pyeloplasty from 2018 to 2019, and a sex- and age-matched control group of healthy children. Serum blood urea nitrogen and creatinine levels were normal in all patients. The whole urine and urinary exosomal concentrations of MXRA5 were measured by enzyme-linked immunosorbent assay. The correlations between bladder/renal pelvic MXRA5 levels and differential renal function (DRF) in the affected kidney were also tested. A total of 35 UPJO patients and 12 controls were enrolled in the study. There was no significant difference in whole-urine MXRA5 levels between the controls and UPJO patients. However, exosomal MXRA5 levels were significantly lower in the controls compared with patients with UPJO (p<0.05). There were non-significant correlations between bladder and renal pelvis whole-urine MXRA5 levels and DRF (R2=0.1115, p=0.05 and R2=0.3313, p=0.0502, respectively). The strongest correlation was between exosomal MXRA5 level in the renal pelvis and DRF (R2=0.8128, p<0.0001). Urinary exosomal MXRA5 levels were significantly increased in children with UPJO. Higher urinary exosomal MXRA5 levels were also significantly correlated with decreased DRF in the affected kidney in cases of UPJO.